Single Institution Experience with Lumbar Drainage and Subarachnoid Hemorrhage - Coggins, William S.; Banko, Lauren E.; Chokhani, Purav; Rushing, Elise G.; Necarsulmer, Julie; Sasaki-Adams, Deanna (Journal of Neurological Surgery Part B: Skull Base, 2024)
Introduction In our article, we evaluate the effect of lumbar drainage on delayed cerebral ischemia and requirements for permanent cerebrospinal fluid diversion in patients with aneurysmal subarachnoid hemorrhage.Methods We performed a retrospective cohort study from 2014 to 2023 at the University of Arkansas for Medical Sciences (UAMS) examining factors associated with patients (n = 150) who had aneurysmal subarachnoid hemorrhage and a lumbar drain placed. The main outcomes examined were incidence of delayed cerebral ischemia, need for permanent cerebrospinal fluid diversion, and neurologic outcomes at discharge that were compared to currently published standards.Results We failed to appreciate a reduced occurrence of delayed cerebral ischemia (37.3% with the current literature supporting rates of 20–30%); however, we did find a low rate of requiring permanent cerebrospinal fluid diversion (12% compared to 10–20% in the current literature) with overall good neurologic outcomes at discharge (∼69% of patients had a Glasgow Outcome Scale [GOS] of 4–5 at discharge). Patients with GOS ≥ 4 at discharge were noted to be more likely to have more days or lumbar drainage and less likely to be older than 65 years, have had an external ventricular drain placed, and have experienced delayed cerebral ischemia.Conclusion Lumbar drainage is a potentially useful adjunct in the management of secondary neurologic injury in subarachnoid hemorrhage.
Keywords: lumbar drain; subarachnoid hemorrhage; vasospasm; delayed cerebral ischemia; aneurysm